Survei Keterampilan Dasar Futsal Usia 16 Tahun - Ibnu Prasetyo Widiyono; Ahmad Khozin Munadi (Departement of Mathematics Education, 2024)
This research aims to determine the futsal playing skills of the Swallow Young Futsal Academy U-16 Kebumen players in 2023. The research carried out is a quantitative description research with two variables. The subjects in this research were the Swallow Young Futsal Academy U-19 Kebumen players with a total of 17 participants. The method used is a survey method, the sampling technique uses purposive sampling. The data technique uses a regression correlation test. Based on the results of the futsal skills test held in December 2023, as many as 17 male participants at the Swallow Muda Futsal Academy U-19 club received the following data: 0 children (0%) were declared Very Good, 4 children ( 24%) stated Good, 8 children (47%) stated Fair, 5 children (29%) stated Poor, and 0 children (0%) stated Very Poor. Meanwhile, the maximum value (longest time) is 84 and the minimum value (fastest time) is 47 with an average of 67. Based on the guidelines, the degree of relationship shows that the level of relationship is very strong. Based on these results, it can be concluded that there is a significant influence on the level of playing skills at the Kebumen U-19 Futsal Academy Youth Swallow.